Impact of diet on incisor growth and attrition and the development of dental disease in pet rabbits. (19th March 2015) - Meredith, A. L.; Prebble, J. L.; Shaw, D. J.
<x xml:space="preserve">Abstract</x> OBJECTIVES To assess the impact of four rabbit diets (hay only; extruded diet with hay; muesli with hay; muesli only) on length and curvature of cheek teeth and eruption and attrition rates of incisors. MATERIALS AND METHODS Thirty‐two Dutch rabbits, randomly divided into four diet groups, had length and saggital plane curvature of the first cheek teeth measured radiographically at 1, 9 and 17 months. Eruption/attrition of the left upper incisor was directly measured at weeks 30, 32 and 35. RESULTS Eruption rates matched attrition rates in all groups, but were higher in the hay only group than in both groups fed muesli. By month 9, a greater degree of tooth curvature was present in rabbits fed muesli only than in those fed hay only and extruded diet with hay. After 17 months, rabbits fed muesli only and muesli with hay had longer lower first cheek teeth and larger interdental spaces between the first two molars than rabbits fed extruded diet and hay and hay only. Three rabbits fed muesli only developed evidence of dental disease. CLINICAL SIGNIFICANCE Presence of increased tooth length, curvature and interdental spaces indicated early dental pathology in rabbits fed muesli. Muesli diets cannot be recommended for pet rabbits.